Abiotic factors affecting Diachasmimorpha longicaudata (Hymenoptera: Braconidae) activity as a natural enemy of Ceratitis capitata (Diptera: Tephritidae) under semi‐natural conditions in the Mediterranean region. (18th May 2018) - Harbi, A.; Beitia, F.; Chermiti, B.; de Pedro, L.; Ferrara, F.; Asís, J. D.; Polidori, C.; Tormos, J.; Sabater‐Muñoz, B.
Abstract: The larval–pupal endoparasitoid Diachasmimorpha longicaudata (Hymenoptera: Braconidae) is currently the most commonly employed biological control agent against Tephritid fruit flies in the Americas. However, this parasitoid remains largely ignored and is not used in many regions, including the Mediterranean Basin. In this study, the potential of D. longicaudata as a biocontrol agent against the Mediterranean fruit fly (medfly) Ceratitis capitata (Diptera: Tephritidae) was addressed in an area of eastern Spain (the Valencian community). The parasitic activity of parasitoids and the effects of climatic conditions were evaluated throughout a 1‐year period in field‐cage experiments in which parasitoids were confined with apples artificially infested with medfly larvae. The following parameters were calculated and related statistically to several environmental conditions: the parasitism rate, the induced mortality and progeny sex ratio. The results show that D. longicaudata is able to parasitize medfly larvae throughout the year under semi‐natural conditions. Important fluctuations in the parasitism rate (from almost zero to 42%) and the induced mortality (from 6% to 80%) were partially influenced by climatic conditions. The parasitism rate increased with mean temperature and decreased with mean relative humidity, while the induced mortality decreased with minimum relative humidity. The optimal climatic conditions for the activity of the parasitoid were a mean temperature of 16–24°C combined with a relative humidity of 45%–60%. Overall, these results suggest that reduction in the medfly population due to D. longicaudata activity is feasible and provide information about the optimal time period for parasitoid release in the field. In conclusion, D . longicaudata has a significant potential to control C. capitata in the Mediterranean region.